Oxido‐peroxido W(VI)‐histidine–MgAl‐layered double hydroxide composite as an efficient catalyst in sulfide oxidation. (17th April 2018) - Nikkhoo, Mohammad; Amini, Mojtaba; Morteza, S.; Farnia, F.; Bayrami, Arshad; Bagherzadeh, Mojtaba; Gautam, Sanjeev; Chae, Keun Hwa
Abstract : Oxido‐peroxido W(VI)‐histidine–MgAl‐layered double hydroxide composite was prepared by using MgAl‐layered double hydroxide as a host and oxido‐peroxido W(VI)‐histidine complex as a guest. The composite was characterized by XRD, IR, EDX, SEM and TEM techniques. This composite is tested for catalytic selective sulfoxidation reactions using hydrogen peroxide as oxidant showing good to moderate conversion along with high selectivity. Abstract : Oxidation of various sulfides in the presence of oxido‐peroxido W(VI)‐histidine–MgAl‐layered double hydroxide composite as an efficient catalyst were studied.